Hazardous drinkers in the accident and emergency department—Who accepts advice?. Issue 4 (18th June 2004) - Patton, R; Crawford, M; Touquet, R
Abstract : Aims: To identify factors that predict acceptance of brief advice among people consuming excessive alcohol in an accident and emergency (A&E) department. Methods: Patients presenting to an A&E department were screened using the Paddington Alcohol Test. All patients identified as hazardous drinkers were offered advice about their drinking. Data were collected on patients' age, sex, presenting condition, and alcohol consumption. Binary logistic regression was used to identify variables that predicted acceptance of the offer of advice. Results: The presenting condition, together with the total number of units consumed on a single occasion, predict the uptake of an offer of help. Conclusions: Patients identified as hazardous drinkers who present after a fall, head injury, or other accident are less likely to accept help. Clinicians should emphasise the potential relation between alcohol consumption and health related consequences to encourage the uptake of advice for these patients.